Society and culture with family planning - Ecoben, Wenceslao B.; Palparan, Alicia M. (Mandaluyong City : Books Atbp. Publishing Corp., 2015)
"The authors provide necessary and useful tools in learning society and culture which, hand in hand, help the students of the new generation learn better based on past experience. This makes a better understanding of man's world as it evolved in time."
Includes bibliography.
English text.
Keywords: Society; Culture; Family planning